Religious Character Building Through Islamic Personal Development Activities at SMP IT Fathonah Baturaja - Amilda Amilda (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article discusses Religious Character Building through Islamic Personal Development Activities at SMP IT Fathonah Baturaja, Ogan Komering Ulu Regency, South Sumatra. This qualitative research uses data from the field through observations, interviews, and documents. In this study, researchers used a qualitative descriptive approach. They obtained data in the form of written and spoken words and explained them in detail and detail—data collection techniques in this study through interviews, observation, documentation, and triangulation. Data analysis techniques start from data collection, presentation, and verification. From the study results, it can be concluded that the implementation of fostering students' religious character through Islamic personal development activities at SMP IT Fathonah has gone well. This activity starts from the initial understanding or planning process carried out to provide a good understanding as a provision for giving character to students, and its implementation is carried out with the right strategy and participation from existing stakeholders, both foundations, teachers, students, and parents. Furthermore, the process is through habituation or implementation, which consists of habituating discipline on time by accustoming children to pray together, accustoming children to pray, as well as other habituation. Islamic Personal Development Activities To see how this program is running, whether the activities have run according to the plan that has been set, how the presence of students or teachers in the process of activities, or see obstacles in the implementation process, of course, evaluation activities are important activities carried out by the school.